Prevalence of autoimmune hemolytic anemia in ulcerative colitis - Al-Khazraji, Khalid A. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Ulcerative colitis is a chronic idiopathic inflammatory disorder that affects the rectum & extends proximally to affect variable extent of the colon. Autoimmune hemolytic anemia had reported in few cases. Objective: to determine the prevalence of autoimmune hemolytic anemia in Ulcerative colitis. Patient & Methods: Fifty Iraqi patients having Ulcerative colitis attending the GIT Center in Baghdad during the period from March to August 2004 were interviewed, examined and diagnosed according to pathological study done for colonic biopsies by the same centre. Blood was drown for the assessment of complete picture with blood film, reticulocyte percent, erythrocyte sedimentation rate, Coombs test (direct, indirect), antinuclear antibody, immunoglobulin assay, serum iron and TIBC in the same laboratory unit. Results: In our study, 18(36%) patients were anemic, fifteen of them had normal or low reticulocyte percent with normochromic normocytic RBC in blood film, probable causes of anemia was either iron deficiency proved by low serum iron and high total iron binding capacity (TIBC), or anemia of chronic illness. The remaining three of eighteen patients with reticulocytosis, two of them Coombs test were negative and normal film, but they were having acute bloody diarrhea which probably was the cause of reticulocytosis. The third patient was Coombs positive with features of hemolytic anemia in the blood film (polychromic with spherocytosis), this patient had also a high titer of IGg, LDH, so that this female had all the evidence of autoimmune hemolytic anemia which is a rare complication of Ulcerative colitis. Salfasalazine as a treatment of Ulcerative colitis can cause autoimmune haemolysis, but in this case the drug had stopped for one month before the development of autoimmune haemolysis. In our sample we had five patients with reticuloytosis but normal haemoglobin level and normal blood film with cooms negative (direct and indirect) those five patients might had nonimmune causes of hemolytic like G6PD deficiency which need further investigations, or might had bloody diarrhea which cause elevated reticulocyte as areaction to blood loss, or it may be due to salazopyrine effect which may lead to increase level of reticulocyte. Conclusion:Most studies giving range of autoimmune haemolytic anaemia with Ulcerative colitis between 1%-2%, all these studies showed direct coomb’s test positive, and our study showed 2% incidence. So it is one of the rare manifestations of Ulcerative colitis. It does not depend much on severity, duration and degree of colonic involvement.